Investigation of machining mechanism of monocrystalline silicon in nanometric grinding - Liping He (AIP Advances, 2017)
Monocrystalline silicon is the foundation of the computer industry, so it has a great significance to study the ultra-high precision machining of silicon. Molecular dynamics has been proved as a very effective method for the study of ultra-precision machining in nanoscale. During the grinding of brittle materials in nano-level, there are some unique phenomena such as brittle-ductile transition. To study the machining mechanism in nanometric grinding of monocrystalline silicon, the subsurface damage of < 0 0 1 > oriented Monocrystalline silicon under different grinding speeds were investigated by means of molecular dynamics simulations. The interactions between different atoms are described by the Morse and Tersoff potential. Based on analyzing the mechanism of diamond tool extrusion induced silicon lattice slip and distortion, the grinding process is explained. The movement of atoms and phase transformation are studied. The results show that there is not enough time for atoms beneath the tool to rearrange when increasing grinding speed at a low speed, which leads to the subsurface damage thickness decreases. When the diamond tool radius is small enough but still bigger than the undeformed chip thickness, the brittle-ductile transition can be achieved in the grinding region. And during the grinding process, the normal force is smaller than the tangential force. However, when the radius of the diamond tool increases to a certain value, the normal force could be larger than the tangential force.